The Application of A Contextual Approach in Indonesian Learning About Writing Exposition Text - Cherien Ayu Oktaviany; Vebbi Andra; Hengki Satrisno (Yayasan Karinosseff Muda Indonesia, 2022)
Indonesian language learning can not be separated from the methods of approach in the delivery of materials in this case one of the approaches used is contextual approach. The implementation of this approach must have inhibitory factors and supporting factors. The purpose of this research was to find out how the implementation of the application, inhibitory factors and supporting factors contextual approach in learning Indonesian text material exposition students Class X IPA 3 SMA 1 Negeri Kinali. This type of research is descriptive qualitative. Data collection by conducting observations of teachers, students and classes, interviews and documentation. The subjects of this study were Indonesian language teachers and X IPA 3 grade students. Data validity technique is triangulation of sources by means of data suppression obtained. Based on the results of research conducted by researchers to teachers and students of Grade X IPA 3 SMA 1 Negeri Kinali. That the implementation of contextual approach is implemented ideally this has been proven by the existence of research interviews to teachers, students and monitoring carried out when the teaching and learning process takes place and the supporting factors are enthusiastic learners in following the learning, as well as adequate facilities and pre-facilities and inhibitory factors are lack of time and lack of materials delivered.